Magnitude of the protonmotive force in respiring Staphylococcus aureus and Escherichia coli. - Collins, S H (1976)
The membrane potential and pH gradient developed across the plasma membranes of whole cells of Staphylococcus aureus and spheroplasts of Escherichia coli were estimated. The distributions of potassium ions in the presence of valinomycin and the pH gradient across the membrane were determined from the changes in pK and pH observed in the external medium during transition from the energized respiring state to the de-engerized resting condition. The protonmotive force in respiring cells was estimated at 211 mV for S. aureus and 230 mV for E. coli at external pH values of approximately 6.5. The adequacy of these protonmotive forces as a driving force for substrate accumulation or adenosine 5'-triphosphate synthesis is discussed.